2019
DOI: 10.1038/s41467-018-08238-y
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake lubrication and healing explained by amorphous nanosilica

Abstract: During earthquake propagation, geologic faults lose their strength, then strengthen as slip slows and stops. Many slip-weakening mechanisms are active in the upper-mid crust, but healing is not always well-explained. Here we show that the distinct structure and rate-dependent properties of amorphous nanopowder (not silica gel) formed by grinding of quartz can cause extreme strength loss at high slip rates. We propose a weakening and related strengthening mechanism that may act throughout the quartz-bearing con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 58 publications
1
47
0
Order By: Relevance
“…In general, these processes (thermo-poro-mechanical pressurization, melt lubrication, crystal plastic grain-size-and temperature-dependent deformation mechanisms, etc.) determine dynamic weakening of the slip zone (Di Toro et al, 2011;Green et al, 2015;Rice, 2006;Rowe et al, 2019).…”
Section: Markers Of Fast Accelerated Slip In Natural Rocksmentioning
confidence: 99%
“…In general, these processes (thermo-poro-mechanical pressurization, melt lubrication, crystal plastic grain-size-and temperature-dependent deformation mechanisms, etc.) determine dynamic weakening of the slip zone (Di Toro et al, 2011;Green et al, 2015;Rice, 2006;Rowe et al, 2019).…”
Section: Markers Of Fast Accelerated Slip In Natural Rocksmentioning
confidence: 99%
“…By investigating deformed fault rocks in the slip zones of natural and experimental faults, a range of mechanochemical processes has been recognized as important in mineral amorphization, including frictional melting (Di Toro et al, 2006; Sibson, 1975), comminution of clasts (Janssen et al, 2010; Ozawa & Takizawa, 2007; Pec et al, 2012, 2016; Toy et al, 2015; Wenk, 1978; Yund et al, 1990), and mechanically activated disassociation and subsequent precipitation of carbonaceous solids (Delle Piane et al, 2018). Recently, it was suggested that AMs may be responsible for fault lubrication and healing (Rowe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous physical and chemical processes have been theoretically and experimentally proposed to justify fault lubrication during seismic slip, for example, flash heating (Beeler et al, 2008;Goldsby & Tullis, 2011;Rice, 2006), powder lubrication (Han et al, 2010;Reches & Lockner, 2010), frictional melting Spray, 2005), silica gel formation (Di Toro et al, 2004), elastohydrodynamic lubrication (Brodsky & Kanamori, 2001;Cornelio et al, 2019), grain size-and temperature-dependent processes (De Paola et al, 2015;Green et al, 2015;Rowe et al, 2019;Spagnuolo et al, 2015), and thermal decomposition (Collettini et al, 2013;Han et al, 2007). In particular, on a fault patch in silicate-built rocks, flash heating and melting (Goldsby & Tullis, 2011), or grain fragmentation of the rock (Chen et al, 2017a;De Paola et al, 2015;Green et al, 2015;Rowe et al, 2019;Spagnuolo et al, 2015) may occur during the initial stages of seismic slip at the passage of the earthquake rupture propagation front. With progressive slip, the continuously generated melt droplets can accumulate to form a continuous melt layer possibly resulting in melt lubrication (Shimamoto, 2005;Spray, 1995).…”
Section: Introductionmentioning
confidence: 99%